2020
DOI: 10.1002/cctc.201901533
|View full text |Cite
|
Sign up to set email alerts
|

Short‐time Thermal Oxidation of Ultrathin and Broadband Carbon Nitride for Efficient Photocatalytic H2 Generation

Abstract: Broadband light absorption and excellent charge separation/migration efficiency are two important indicators for promising photocatalyst. However, realizing the above two aspects simultaneously is still a challenge. Here, an ultrathin and broadband carbon nitride (UBCN) is synthesized via a short‐time thermal oxidation process. The as‐prepared UBCN exhibits outstanding photocatalytic H2 generation activity (240.60 μmol h−1) under irradiation with λ>400 nm. Moreover, UBCN can work under irradiation with a longe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…Moreover, Mo et al . evidently confirmed that the ultrathin and broadband carbon nitride was successfully prepared by short‐time thermal oxidation for photocatalytic H 2 generation . The as‐prepared ultrathin and broadband carbon nitride exhibited outstanding photocatalytic H 2 generation activity of 240.60 μmol/h under irradiation with λ > 400 nm.…”
Section: Figuresupporting
confidence: 60%
“…Moreover, Mo et al . evidently confirmed that the ultrathin and broadband carbon nitride was successfully prepared by short‐time thermal oxidation for photocatalytic H 2 generation . The as‐prepared ultrathin and broadband carbon nitride exhibited outstanding photocatalytic H 2 generation activity of 240.60 μmol/h under irradiation with λ > 400 nm.…”
Section: Figuresupporting
confidence: 60%
“…1b-d, and S1 †) shows that the melon is constituted by glassy bulky flakes, which is consistent with the literature. 35 Similar to the melon, the PHI has a bulky morphology, however with an obvious circular porous structure and thus a rougher surface. Comparatively, the PTI has a hollow tube structure with a length of several micrometers, a horizontal width of approximately 500 nm and a wall thickness of around 100 nm.…”
Section: Resultsmentioning
confidence: 99%
“…However, there is a significant decrease in the intensity of the peak at 1100–1600 cm −1 , indicating a change in aromatic CN or C–N species. 35 Additionally, the presence of abundant –OH species near 3500 cm −1 suggests a strong correlation between improved hydrophilic properties of bulk CN. 36 Fig.…”
Section: Resultsmentioning
confidence: 99%